Antibiotic use for digestive system diseases (ICD-10: K00-K93) at an Indonesian government teaching hospital in 2021 - Rahmah Inasiyyah; Ikhwan Yuda Kusuma; Fauziah Fauziah; Fiqih Nurkholis; Khamdiyah Indah Kurniasih (International Journal of Gastrointestinal Intervention)
Background: Digestive system diseases pose a significant global health challenge. In many developing countries, inappropriate antibiotic use is common, and the COVID-19 pandemic further disrupted standard antibiotic prescribing practices. This study evaluated antibiotic prescribing patterns for digestive system diseases in a major Indonesian hospital during 2021. Methods: We conducted a retrospective, observational analysis of antibiotic prescriptions for 47,698 inpatients with digestive system diseases at Cilacap Government Teaching Hospital, Indonesia, throughout 2021. Data were extracted from electronic medical records and analyzed based on patient demographics, International Classification of Diseases, 10th revision classifications, World Health Organization Access, Watch, and Reserve categories, and routes of administration. Statistical analyses and visualizations were performed using Microsoft Excel (Microsoft) and R Studio (Posit). Results: Among 2,183 patients diagnosed with digestive system diseases, the majority were active adults, with a predominance of male patients. The most frequently prescribed antibiotics belonged to the “Watch” group. Acute appendicitis (n = 416), inguinal hernia (n = 250), and functional dyspepsia (n = 169) were the leading diagnoses. Antibiotic administration was more prevalent among females for these conditions, despite higher overall antibiotic use for digestive system diseases among males. Cases peaked at 319 in December and dropped to 65 in July. The dry season months recorded fewer cases (July: 65, August: 129). The most prescribed antibiotics were ceftriaxone (n = 638), metronidazole (n = 486), and cefazolin (n = 216), indicating a predominant use of broad-spectrum agents. Conclusion: The study reveals a high reliance on broad-spectrum antibiotics, particularly those in the “Watch” group, suggesting potential overuse. These findings underscore the need for improved antibiotic stewardship practices, especially in regions facing the compounded challenges of the COVID-19 pandemic.